2011
DOI: 10.1111/j.1471-4159.2011.07230.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandin E2 in the synthesis of the pro‐inflammatory cytokine interleukin‐6 in primary sensory neurons: an in vivo and in vitro study

Abstract: Following various types of nerve injury, cyclooxygenase 2 and prostaglandin E2 (PGE2) are universally and chronically upregulated in injured nerves and contribute to the genesis of neuropathic pain. Persistent high levels of PGE2 likely exert chronic effects on nociceptive dorsal root ganglion (DRG) neurons. In the present study, we tested the hypothesis that injured nerve-derived PGE2 contributes to the up-regulation of the pro-inflammatory cytokine interleukin-6 (IL-6) in DRG neurons following partial sciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 52 publications
3
46
1
Order By: Relevance
“…10,17 Indeed, peripheral nerve injury induces the increase in IL-6 in both the DRG and spinal cord, which is in agreement with our results. The increase in IL-6 may be linked to various pathways including the activation of EP4 receptors by prostaglandin 2 18 and signaling pathways involving the TNF-α receptor and nuclear factor κB. 19 It is plausible that SCS modulates the activation of these pathways and reduces the expression of IL-6 in the DRG.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 Indeed, peripheral nerve injury induces the increase in IL-6 in both the DRG and spinal cord, which is in agreement with our results. The increase in IL-6 may be linked to various pathways including the activation of EP4 receptors by prostaglandin 2 18 and signaling pathways involving the TNF-α receptor and nuclear factor κB. 19 It is plausible that SCS modulates the activation of these pathways and reduces the expression of IL-6 in the DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Early animal studies have shown that there is a local increase in IL-6 mRNA and protein levels following peripheral nerve injury [6063]. Further studies have suggested that the upregulation of IL-6 may be through a prostaglandin E2-stimulated pathway [64,65]. However, in a rat nerve compression experiment, onset of allodynia immediately followed the compressing injury, whereas IL-6 elevation was delayed [66].…”
Section: Targeting Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…15,19 Our body produces antiinfl ammatory such as cortisol, thus to keep in homeostasis, our body has the propensity to compensate noxious stimuli, proinflammatory mediators or neutralize antigens by itself. 5,8,9 Based on Psychoneuroimmunology concept, in stressful individuals, cortisol level increased and plays a synergistic role with proinfl ammatory cytokines instead of suppressing them. 12,15,16 This idea was supported with the facts that antidepression therapy relieves the pains.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the prevalence of persistent pain occurred in the maxillary teeth were 87.5% compared to 12.5% in the mandibular teeth, and 68.8% relieved by tricyclic depressants. 6 Conventionally, relieving pain with drugs targeting biological factors by lowering the "pain triggers" mediators such as prostaglandins (PGs) [7][8][9] or tumor necrosis α (TNF-α). 10 Nevertheless, prolonged or abuse of these drugs have adverse effects.…”
Section: Introductionmentioning
confidence: 99%